Experimental and numerical investigation of interply hybrid composites based on woven fabrics and PCBT resin subjected to low-velocity impact. (15th November 2015) - Yang, Bin; Wang, Zhenqing; Zhou, Limin; Zhang, Jifeng; Liang, Wenyan
Abstract: Low-velocity impact response of interply hybrid composites based on glass and carbon woven fabrics as reinforcement and polymerized poly (butylene terephthalate) (PCBT) as matrix was presented in this paper. Experiment and finite element method (FEM) were respectively performed to investigate the hybridization effect on the composites under impact velocity of 3 m/s, 5 m/s and 7 m/s. Specimens used in the experiment were made by vacuum assisted prepregs process (VAPP). All the material parameters used in simulation were determined by experimental test. Three-dimensional finite element models were developed in ABAQUS/Explicit to analyze the damage behavior of interply hybrid composite laminates, and a user subroutine VUMAT was compiled for the woven fabrics reinforced PCBT composites. Experimental results show that hybrid composites at hybrid mass ratio of 37:63 could absorb more energy in the impact event compared with pure composites, and the perforation thresholds enhance significantly. The simulation results are well agreed with experimental results. The damage mode of the interply hybrid composites under low-velocity impact is further discussed.